2019
DOI: 10.3390/pharmaceutics11060274
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of a Multi-Layered Polypill Containing Six Drugs Using a Novel Stereolithographic Method

Abstract: Three-dimensional printing (3DP) has demonstrated great potential for multi-material fabrication because of its capability for printing bespoke and spatially separated material conformations. Such a concept could revolutionise the pharmaceutical industry, enabling the production of personalised, multi-layered drug products on demand. Here, we developed a novel stereolithographic (SLA) 3D printing method that, for the first time, can be used to fabricate multi-layer constructs (polypills) with variable drug con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
165
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(171 citation statements)
references
References 64 publications
4
165
0
2
Order By: Relevance
“…Dissolution tests showed that the polypill geometry and the type of excipient affected the drug release allowing distinct release profiles for each of the six drugs. This study showed the possibility to use SLA 3DP for fabricating multi-drugs tablets to improve personalisation for patients [14].…”
Section: Stereolithography (Sla)mentioning
confidence: 88%
“…Dissolution tests showed that the polypill geometry and the type of excipient affected the drug release allowing distinct release profiles for each of the six drugs. This study showed the possibility to use SLA 3DP for fabricating multi-drugs tablets to improve personalisation for patients [14].…”
Section: Stereolithography (Sla)mentioning
confidence: 88%
“…An important consideration when developing polypills regards the allocation of the APIs in the different layers; the top and the bottom layers will expose a larger area to the media and, therefore, drugs in those layers will be released faster. An effective strategy can be to include the less soluble APIs in the external layer, and the more soluble in the inner ones [34].…”
Section: Pressure-assisted Microsyringe 3d Printingmentioning
confidence: 99%
“…Główne korzyści wynikające z wprowadzenia metod druku 2D i 3D do wytwarzania postaci leku stanowią: -wysoka wydajność i powtarzalność procesu, minimalizacja strat oraz możliwość wytwarzania niewielkich partii produktów leczniczych, -sporządzanie preparatów o ściśle określonej zawartości substancji leczniczej, łatwa modyfikacja dawki, -nadanie drukowanemu obiektowi złożonych kształtów niemożliwych lub bardzo trudnych do otrzymania tradycyjnymi metodami [36], -wytwarzanie preparatów kilkuskładnikowych o modyfikowanym uwalnianiu substancji leczniczych [27,30], -dostosowanie składu preparatu pod względem rodzaju i ilości substancji pomocniczych dla określonej grupy wiekowej pacjentów lub w przypadku ryzyka wystąpienia alergii i nietolerancji [32], -możliwość modyfikacji smaku, koloru, rozmiaru i kształtu postaci leku zależnie od preferencji i zdolności pacjenta do jej przyjęcia [37]. W piśmiennictwie coraz częściej zwraca się uwagę na możliwość wytwarzania tą metodą nie tylko leków produkowanych przez przemysł, Tabela 4.…”
Section: Porównanie Metod Druku 2d I 3dunclassified
“…Duża możliwość modyfikacji składu formulacji [25] i szybkości uwalniania substancji czynnej [26] Niższa wytrzymałość mechaniczna drukowanych tabletek w porównaniu produktami otrzymanymi przez kompresję proszków [26]. Konieczność uzyskania gładkiej i homogennej pasty [27]. Ryzyko obecności resztek rozpuszczalników w wydrukowanym produkcie [36].…”
Section: Ekstruzja W Temperaturze Pokojowejunclassified